2021
DOI: 10.4149/neo_2021_210304n276
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of AHNAK2 restricts thyroid carcinoma progression by inhibiting the Wnt/β-catenin pathway

Abstract: AHNAK nucleoprotein 2 (AHNAK2) has been proposed to have an oncogenic role in various human cancers. However, the functional role of AHNAK2 in thyroid carcinoma (TC) progression has never been explored. In this study, quantitative real-time polymerase chain reaction and western blot were conducted to evaluate the expression of genes. The functional role of AHNAK2 was elucidated by cell count kit-8, colony-forming assay, wound healing assay, and Transwell invasion assay. We found that AHNAK2 was highly expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…A positive association between Wnt target biological pathways, and the PS-score was identified previously. Among the pyroptosis-related signature genes, AHNAK2 knockdown was previously reported to inhibit the Wnt pathway ( Lin et al, 2021 ). In addition, AHNAK2 expression was reported to be significantly positively correlated with the PS-score in TCGA and two GEO-BC cohorts ( Figures 8A–C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive association between Wnt target biological pathways, and the PS-score was identified previously. Among the pyroptosis-related signature genes, AHNAK2 knockdown was previously reported to inhibit the Wnt pathway ( Lin et al, 2021 ). In addition, AHNAK2 expression was reported to be significantly positively correlated with the PS-score in TCGA and two GEO-BC cohorts ( Figures 8A–C ).…”
Section: Resultsmentioning
confidence: 99%
“…Wnt signaling is an essential biological process, which plays critical roles in tumorigenesis and prognosis ( Reya and Clevers 2005 ). Among the DEGs between distinct pyroptosis-related subtypes, AHNAK2 knockdown was previously reported to activate the Wnt pathway and correlated with tumor immune cell infiltration while its role in BC is rarely reported ( Lin et al, 2021 ; Zheng et al, 2021 ). We found a significant positive association between AHNAK2 expression and the PS-score.…”
Section: Discussionmentioning
confidence: 99%
“…proposed that Del-AHNAK2 mut increased the TMB and NAL level, activated cytotoxic T lymphocyte (CTL) effector functions and interferon-gamma (IFN)-γ signaling, and eventually initiated the therapeutic immune response of NSCLC ( 39 ). AHNAK2 knockdown was previously reported to activate the Wnt pathway and correlated with tumor immune cell infiltration thyroid cancer ( 40 ).…”
Section: Discussionmentioning
confidence: 97%
“…Lin et al reported that the knockdown of AHNAK2 restrained EMT in thyroid carcinoma in vitro by regressing the Wnt/β-catenin signaling pathway. 11 Liu et al showed that AHNAK2 promotes EMT in lung cancer via the TGF-β/Smad3 pathway. 12 TGF-β1 induces the upregulation of EMT-related genes, promoting tumor cell migration and invasion.…”
Section: Introductionmentioning
confidence: 99%
“…The main underlying mechanism is epithelial–mesenchymal transitions (EMT). Lin et al reported that the knockdown of AHNAK2 restrained EMT in thyroid carcinoma in vitro by regressing the Wnt/ β ‐catenin signaling pathway 11 . Liu et al showed that AHNAK2 promotes EMT in lung cancer via the TGF‐ β /Smad3 pathway 12 .…”
Section: Introductionmentioning
confidence: 99%